Validity of the Rotation Type Blended Learning Model Using the M-Learning Application for Athletes of Student Sports Education and Training Center - Rezaini, Mulki Siti Hajar; Ruhiat, Yayat; Nulhakim, Lukman (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This study aimed to evaluate the validity of a rotational blended learning model incorporating the M-Learning application, specifically designed for Student Sports Education and Training Center athletes. The M-Learning platform enables flexible, anytime-anywhere learning tailored to meet the unique needs of athlete students, addressing challenges related to their demanding training schedules and academic engagement. This research adopts a Research and Development (RD) methodology, utilizing the ADDIE model, which includes the phases of Analysis, Design, Development, and Implementation. Data were collected through expert validation sheets and response questionnaires. Quantitative analysis was conducted using a four-point Likert scale to determine the feasibility percentage of the model. The results revealed high feasibility ratings from experts: 97.36% for the model, 87.89% for the media, and 94.14% for the material, indicating excellent validity. These findings suggest that the rotational blended learning model with M-Learning is a highly effective and appropriate learning medium for athletes.